ANALISA KINERJA RUAS JALAN DAN FASILITAS PEJALAN KAKI (STUDI KASUS: JALAN WR. SUPRATMAN, DENPASAR) - Ni Made Widya Pratiwi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
ABSTRACT WR. Supratman is the primary collector road, where the land use around is an office, commercial, and settlement area. Segment between WR. Supratman - Gadung to the intersection of WR. Supratman - Kamboja - Seruni Street, there are frequent traffic congestion problems. When viewed from the segment of the segment there are RSU Puri Raharja, Unit Rawat Jalan RSU Puri Raharja, Mosque, and the Police of Bali Region which of course cause high pedestrian movement. Therefore, there is also an analysis of pedestrian facilities, thus providing a sense of security and comfort for pedestrians. The data required in this study are primary data obtained from survey results to the field. From the analysis result obtained WR. Supratman the densest movement on the working day (weekday) occurred at 17:00 to 18:00 WITA with traffic volume of 2598.2 pcu/hour, with a value of V/C Ratio of 0.83 so that the level of service road segment including the category "D". Vehicles velocity on WR Road. Supratman on working days is 23.65 km/h. Result of performance analysis of WR. Supratman's segment most busy movement on a weekdend occurs at 12:30 to 13:30 pm with a traffic volume of 2180.6 pcu/hour, with a value of V / C Ratio of 0.870 so that the level of road service is categorized as "C". Speed of vehicle on WR Road. Supratman on holiday is 26.43 km / hour. Based on the results of analysis, for pedestrian facilities recommended Pelican Crossing is installed as a crossing facility people. Key word: pedesterian, road performance